A Brief History of Chemical Reactor and Reaction Technology. Issue 7 (13th May 2019) - Kockmann, Norbert
Abstract: The term "chemical reactor" appears for the first time in open literature at the end of First World War, while in Germany the term "reaction technology" was coined in the 1950s, although chemical reactions and processes have been known for thousands of years. In the early days, reactors were furnaces and pots, which specialized further over the centuries. With the Industrial Revolution many reactor types were already known, and industrialization brought an enormous innovation thrust in the field of products as well as technologies. The diversity of reactors today is almost uncomprehensive and so efforts to standardize apparatus are understandable. Abstract : The reactor technology evolved from simple pots and ovens to modern stirred tank and tubular reactors. Product development, process knowledge, material science and simulation tools guided the development to a high variety. Currently, modular design and planning methods lead to standardized equipment.